Process for creation of sustainable web 2.0 based interactive demonstration and content for control education - Updyke, Joshua C. (Kansas State University, 2011)
The objective of this research was to show that controls demonstrations and education can be greatly improved with the use of Web 2.0 tools. First, a user-centered and collaborative website was developed using the freely available Web 2.0 tools. Then procedures for creating animations using control system simulations were developed. Using the Java programming language, interactive graphs were constructed for display to allow the viewer to change the initial conditions of the controls system and plot the results of the simulation as calculated. These animations and interactive graphs used already developed MatLab resources. Using Web 2.0 tools, the collaborative web site can be easily updated by several people simultaneously, only requiring access to the internet. Because of these advantages, collaboration between multiple universities and controls researchers in distant locations is possible, and the new website has the potential of becoming the center of controls research around the world. More importantly, the procedure allows future systems to be demonstrated while requiring minimal additional work, thereby increasing the universities' ability to educate their students, as well as the general public, about controls system research.
Keywords: Web2.0; Controls; Non-Linear; Sustainable; Engineering (0537)